Menyoal Mitigasi Bencana di Negara Berkembang : Studi Mitigasi Bencana di Bangladesh - Marsista Buana Putri (Program Studi Perencanaan Wilayah dan Kota Universitas Pasundan, 2016)
Mitigation is a systematic activity of a state before the disaster occurs until the disaster has occurred, including evacuation and recovery from disasters. Because of the importance of these mitigation activities, especially in developing countries should be responsive to the geographical characteristics of threats and vulnerabilities to disasters. Bangladesh is one of the developing countries have fairly high vulnerability to disasters, particularly natural disasters that occur almost every year as hurricanes / typhoons and floods, and there is no doubt this is happening as a result of geological and geographical factors Bangladesh. Frequent disasters have a direct and significant effect on the development process and the development of Bangladesh, both locally and nationally. How to understand this country responds to the disaster is important to learn and understand. The Bangladesh government to initiate several agencies such as the Disaster Management Bureau (DMB) or Agency / Bureau of Management Disaster local level, the National Council of Management of Disaster or The National Disaster Management Council (NDMC) and the Coordinating Committee of Management of Disaster Inter-Ministry or the Inter-Ministerial Disaster Management Coordination Committee (IMDMCC) at a higher level, which meant that all activities can be coordinated and implemented mitigation as well to maximize all potential and existing resources, including NGOs.